2020
DOI: 10.1111/jcms.13111
|View full text |Cite
|
Sign up to set email alerts
|

UK Parliamentary Scrutiny of the EU Political and Legal Space after Brexit*

Abstract: This article considers the effect of Brexit upon the UK Parliament and whether Brexit will reverse the 'de-parliamentarisation' that has been identified through EU membership. Supporters of Brexit identified an end to ever closer integration, or Europeanisation, and restoration of parliamentary control over repatriated competences as a key benefit of Brexit. Firstly, this article explores how Parliament may adapt to leaving the institutional structures of Europeanisation and whether this may lead to 'de-Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Indeed, Brexit radically reshaped the context of these discussions and the Houses of Parliament are now outside the 'European parliamentary space' created by the Treaties (Cygan et al 2020(Cygan et al : 1610. However, the closer examination of the UK EWS experience still provides valuable insights for both UK and EU stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, Brexit radically reshaped the context of these discussions and the Houses of Parliament are now outside the 'European parliamentary space' created by the Treaties (Cygan et al 2020(Cygan et al : 1610. However, the closer examination of the UK EWS experience still provides valuable insights for both UK and EU stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On one hand, adaptation to the EWS constitutes one of the largest changes to the UK's EU scrutiny systems before the Brexit vote. As the HoP and the UK's devolved legislatures embarks on further changes to these structures after the country's withdrawal, the post-EWS HoP scrutiny frameworks serve as the basis for future development (Cygan et al 2020). In addition, although studies considered the effect of the EWS on UK subnational legislatures (Högenauer 2019(Högenauer , 2017; Borońska-Hryniewiecka 2017), they do not discuss associated administrative adaptation in depth or expand on the implications of these developments regarding the post-Brexit era.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The former focused on political science, economics and law, the latter also drawing in more anthropology, sociology, socio-legal studies and geography. Taken together, UKICE and Governance after Brexit cover a significantly broad range across the UK social sciences (in addition to this special issue, see, for example, the research reported in a Journal of Common Market Studies symposium on 'Impacts of Brexit on Civil Society, Parliament and Access to Justice'; Barnard & Fraser Butlin, 2020;Cygan et al, 2020;Minto, 2020;Wincott, 2020a).…”
Section: The Social Sciences and 'Impact'mentioning
confidence: 99%